THE STUDENTSâ COMPETENCE IN UNDERSTANDING NARRATIVE READING TEXT AT SMAN 1 SOE KABUPATEN TIMUR TENGAH SELATAN (TTS) NUSA TENGGARA TIMUR - Yanpitherszon, Liunokas (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2017)
This research aimed at describing the Â competence of students in understanding narrative reading text at SMAN 1 Soe Kabupaten Timur Tengah Selatan (TTS) NTT. This research used descriptive research method. Â The population of this research is first class of SMAN 1 Soe Kabupaten Timur Tengah Selatan (TTS) NTT in academic year 2014/2015. The total number of population is 142 students in four classes.Â  The researcherÂ  used random sampling technique. There were Â 20 students Â as sample of the research .Â  The writer took 5 students from each class. It used reading test as instrument. The result of the research shows that Based on the studentsâ score in reading narrative text, most of them have low competence in answering the question of narrative text.Â  It is proved by mean studentsâ means score in poor classification, namely 49.3.Â  Based on studentâ answers in the text, it can be seen that there are some studentsâ difficulties in reading narrative text, such as they canât comprehend the part and contents of narrative.